Anti‐Colloidal‐Solutions: Laser‐Generated Nanocrystals in Perovskite: Universal Embedding of Ligand‐Free and Sub‐10 nm Nanocrystals in Solution‐Processed Metal Halide Perovskite Films for Effectively Modulated Optoelectronic Performance (Adv. Energy Mater. 35/2019). Issue 35 (19th September 2019) - Guo, Pengfei; Yang, Xiaokun; Ye, Qian; Zhang, Jin; Wang, Hongyue; Yu, Huiwu; Zhao, Wenhao; Liu, Chen; Yang, He; Wang, Hongqiang
Abstract : In article number 1901341, Hongqiang Wang and co‐workers report that a droplet of laser generated anti‐colloidal‐solution which contains ligand‐free nanocrystals in a desired anti‐solvent can effectively boost the charge transfer of the photogenerated carriers in perovskite solar cells, resulting in a power conversion efficiency of 21.41%, as well as a pronounced stability over 5000 h in relative humidity of 40%.